Cannabidiol as a treatment for craving and relapse in individuals with cocaine use disorder: a randomized placebo‐controlled trial. (9th February 2021) - Mongeau‐Pérusse, Violaine; Brissette, Suzanne; Bruneau, Julie; Conrod, Patricia; Dubreucq, Simon; Gazil, Guillaume; Stip, Emmanuel; Jutras‐Aswad, Didier
ABSTRACT: Background and Aims: Cocaine use disorder (CUD) is a significant public health concern for which no efficacious pharmacological interventions are available. Cannabidiol (CBD) has attracted considerable interest as a promising treatment for addiction. This study tested CBD efficacy for reducing craving and preventing relapse in people with CUD. Design: Single‐site double‐blind randomized controlled superiority trial comparing CBD with placebo. Setting and Participants: Centre Hospitalier de l'Université de Montréal, Canada. Seventy‐eight adults (14 women) with moderate to severe CUD participated. Intervention: Participants were randomly assigned (1 : 1) by stratified blocks to daily 800 mg CBD ( n = 40) or placebo ( n = 38). They first underwent an inpatient detoxification phase lasting 10 days. Those who completed this phase entered a 12‐week outpatient follow‐up. Measurements: Primary outcomes were drug–cue‐induced craving during detoxication and time‐to‐cocaine relapse during subsequent outpatient treatment. Findings: During drug–cue exposure, craving scores [mean ± standard deviation (SD)] increased from baseline by 4.69 (2.89) versus 3.21 (2.78) points, respectively, in CBD ( n = 36) and placebo ( n = 28) participants [confidence interval (CI) = −0.33 to 3.04; P = 0.069; Bayes factor = 0.498]. All but three participants relapsed to cocaine by week 12 with similar risk for CBD ( n = 34) and placebo ( n = 27) participants (hazard ratio = 1.20, CI = 0.65–2.20, P = 0.51; Bayes factor = 0.152). CBD treatment was well tolerated and associated mainly with diarrhoea. Conclusions: CBD did not reduce cocaine craving or relapse among people being treated for CUD.